Cascade substitution reaction between oxabornene and amines to construct cyclohexa‐1, 4‐diene‐3, 6‐diamine and amino alcohol. (19th February 2020) - Zhao, Changkuo; Wang, Xianheng; Xu, Lang; Cao, Ying; Cui, Hanqi; Wang, Yuhe
Abstract: In competition with Michael addition between oxabornene and amines, a cascade substitution reaction predominates to generate cyclohexa‐1, 4‐diene‐3, 6‐diamine and amino alcohol in a moderate yield. This method has wide universality for different amines, overcomes the shortcomings of Michael addition reaction that cannot be synthesized due to shortage of raw materials, and can be further applied to the total synthesis of some related natural products. Abstract :